Analysis of Challenges and Opportunities for Micro, Small, and Medium Enterprises (MSMEs) in the Digital Era in a Systematic Literature Review - Susi Evanita; Zul Fahmi (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
This Systematic Literature Review explores the challenges and opportunities faced by Micro, Small, and Medium Enterprises (MSMEs) in the era of digital technology. This review aims to identify and analyse the challenges and opportunities of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. The research method used was a thorough search of relevant literature using predetermined search criteria, resulting in 320 articles that met these criteria. These articles were further screened based on their relevance to the research questions, and finally, 58 articles were selected for analysis. The results show that the digital era offers significant opportunities for MSMEs, especially in terms of increased access to markets, resources and information. However, MSMEs also face various challenges, including a lack of digital literacy, limited resources, and intense competition. This study highlights the need for MSMEs to embrace digital technology and develop strategies to overcome these challenges. Overall, this systematic literature review provides valuable insights into the challenges and opportunities for MSMEs in the digital era and emphasises the importance of adapting to the changing business landscape. The findings of this research have practical implications for policymakers, MSMEs and other stakeholders interested in MSME development in the digital era.